EVALUATION OF MECHANICAL PROPERTIES OF COIR-ANGUSTIFOLIA HAW AGAVE FIBER REINFORCED HYBRID EPOXY COMPOSITE - Bakri, Bakri; Chandrabakty, Sri; Putra, Kusuma Angga (Jurnal MEKANIKAL, 2017)
This article presents the mechanical properties of coir-angustifolia Hawagave fiber hybrid composite. Prior to form composite, these fibers were soaked in 5%w/v NaOH solution during 24 hours. Coir fibers were twisted and composed one direction like mat and agave fibers were also composed one direction and formed mat. Epoxy resin was used as matrix in this hybrid composite.The hybrid composites were manufactured using hand layup technique followed by compression molding. The variation of fraction volume of coir fiber and agave fiber was 10:20, 15:15 and 20:10 respectively. The tensile strength, tensile modulus, flexural Â strength and flexural modulus were evaluated. Fracture tensile was analysed by Scanning Electronic Microscopy (SEM). Result showed that 15%Vf coir and 15% Vf agave fibers on the hybrid composite yield high tensile strength, tensile modulus and flexural modulus compared to other fraction volume. SEM analysis exhibits that all fraction volume variations on the composite tend to undergo fiber fracture without pull-out and matrix damage.Keywords : hybrid composite, Â coir fiber, angustifolia Haw agave fiber, matrix, mechanical properties.